Assessing the influence of distinct culture media on human pre-implantation development using single-embryo transcriptomics - Ducreux, Bastien; Barberet, Julie; Guilleman, Magali; Pérez-Palacios, Raquel; Teissandier, Aurélie; Bourc’his, Déborah; Fauque, Patricia (Frontiers in Cell and Developmental Biology, 2023)
The use of Assisted Reproductive Technologies (ART) is consistently rising across the world. However, making an informed choice on which embryo culture medium should be preferred to ensure satisfactory pregnancy rates and the health of future children critically lacks scientific background. In particular, embryos within their first days of development are highly sensitive to their micro-environment and it is unknown how their transcriptome adapt to different embryo culture composition. Here, we determined the impact of culture media composition on gene expression in human preimplantation embryos. By employing single-embryo RNA-sequencing after 2 or 5 days of post-fertilization culture in different commercially available media (Ferticult, Global, SSM), we revealed medium-specific differences in gene expression changes. Embryos cultured pre-compaction until day-2 in Ferticult or Global media notably displayed 266 differentially expressed genes (DEGs), which were related to essential developmental pathways. 19 of them could have a key role in early development, based on their previously described dynamic expression changes across development. When embryos were cultured after day-2 in a same media considered more suitable because of its amino acid enrichment, 18 DEGs thought to be involved in the transition from early to later embryonic stages were identified. Overall, the differences were reduced at the blastocyst stage, highlighting the ability of embryos conceived in suboptimal in vitro culture medium to mitigate the transcriptomic profile acquired under different pre-compaction environments.